A Moral Consideration of Corporate-Social-Responsibility (CSR) on the Basis of the Conception of Stephen R. Perry’s Risk, Harm, and Responsibility - Heidinger, Vincent (Journal of Leadership, Accountability and Ethics, 2021)
The goal is to develop a moral consideration of CSR. The nature of risk is examined and a distinction in epistemic conception of probability is introduced. The central question, namely if agent-imposed risk has to be regarded as a form of damage in its own right is introduced and applied to the issue of CSR. The modified question if corporation-imposed risk on society can be viewed as a form of damage comes into play. The terms of avoidability and foreseeability are added to the moral concept. The goal is to show that corporations hold a certain responsibility to society.